THE INFLUENCE OF INTESTINAL MICROBIOTA ON HEPATITIS B: A LITERATURE REVIEW - Silva, Lara Prado; Diniz , Lais de Pádua; Santos, Ana Júlia Moreira; Júnior, Elano Jaime Azevedo; de Oliveira, Danúbio Antonio (CIPEEX, 2024)
This is a literature review that has the objective to understanding the influence of intestinal microbiota on the prognosis of hepatitis B. Searching the Medline, LILACS and IBECS databases for articles published in the last 3 years with descriptors Hepatitis B and dysbiosis. 3 compilations were selected, using suitability to the theme as an exclusion criterion. The increase in non-symbiotic bacteria in the intestine of patients with Hepatitis B, such as Muribaculaceae, is notable, negatively correlating with liver dysfunction, in addition to the increase in harmful bacteria and changes in immune control, with a predominance of regulatory T cells and a decrease in cytotoxic T cells. There is also a change in the composition of the intestinal microbiota in patients with complications of liver cirrhosis resulting from the hepatitis B virus. The microbiota supports the differentiation of B cells through T helpers and CD4+ T lymphocytes, which shows performance in eliminating the hepatitis B virus. The alteration of the intestinal microbiota designates an immunological modification and dysfunction in the intestine-liver axis, which can change the prognostic course of hepatitis B. Thus, in patients with a worse prognosis, an important intestinal dysbiosis was found.